An illustrated introduction to the First World War - Carradice, Phil 1947- (Amberley, 2014)
2014 marks the hundredth anniversary of the First World War, one of the most profound events in human history. People across the world commemorate the fighting and mourn the countless losses every year, eager to ensure that no such tragedy befalls humanity again. This wonderfully illustrated, accessible introduction to the First World War is presented chronologically and breaks down how the war started and how events unfolded, incorporating elements as varied as the poetry and correspondence of those serving to the technological developments that helped make the First World War the first 'modern' war